Genetic variability, heritability and genetic advance in Lentil (Lens culinaris Medik.) - Poudel, Padam Prasad; Aryal, Laxman; Darai, Rajendra; Sah, Rabendra; Subedi, Kumar; Acharya, Basistha; Subedi, Subash; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2022)
The present study was carried out to study the variation, broad-sense heritability, and genetic advance, correlation among traits for growth, yield, and its attributing traits in lentil genotypes. Sixty lentil genotypes were evaluated in augmented design in 2020 at Khajura, Banke. The results indicated that the genotypes were significantly different for days to flowering, days to maturity, 500 seed weight and grain yield kg/ha. The phenotypic coefficient of variation (PCV) was greater than the genotypic coefficient of variance (GCV) for all traits. The 500 seed weight showed the highest PCV (22%) and GCV (21%) whereas days to maturity showed the lowest PCV (5.5%) and GCV (3.2%). The highest value (90%) of heritability (broad sense) was in and lowest (3%) in pods per plant. Genetic Advance Mean 40% was the highest for seed weight but lowest at 1.2% in pods per plant. Grain yield showed a positive and significant correlation in genotypic level with days to maturity (r = 0.7**), plant height (r = 1.66*), pods per plant (r = 1.15**) and seed weight (r = 0.56*). Path analysis found that the seed weight had the most impact on grain yield followed by pod per plant. Thus, selection for yield in lentils through these characteristics would be effective in the varietal developmental program.